Energy Behaviour of Coal Failure under Uniaxial Cyclic Loading/Unloading - Chunlai Wang; Ze Zhao; Chang Zuo (Applied Sciences, 2023)
Coal failure is often the precursor of dynamic disaster. The energy evolution behaviour at different stress values was analysed under the gradation of equal amplitude cyclic loading/unloading. Based on the energy dissipation behaviour, the energy evolution model of the coal specimen was established. The multi-parameter energy behaviour predicting model was proposed. Then, the energy storage factor criterion, the energy tangent factor criterion, the energy dissipation growth factor criterion and the energy damage factor criterion of the coal specimen were proposed during the coal fracture process. The energy density and the energy storage status showed different evolution patterns under cyclic loading/unloading. The energy behaviours and status were different in fracture stages of coal specimens, and the dissipated energy behaviour had a sudden response during the failure process. The energy storage and energy dissipation mechanism were related to their respective limits. The energy storage mechanism showed a growth pattern of “low energy promotion, high energy suppression and dissipation promotion, cumulative suppression”. The damage evolution equation and the energy behaviour evolution criterion were established under the cyclic loading/unloading.